Mathematical modelling of a factory fire - Lee, David Zhi Yi (Nanyang Technological University, 2021)
In this paper, we conduct a case study on factory fires and develop a one-dimensional model for investigating factors leading to spontaneous ignition in a pile of sawdust on top of a hot press. The goal is to approximate the temperature distribution of the layer of sawdust and determine the maximum temperature present, to conclude if there will be spontaneous ignition of the sawdust that leads to a factory fire. The sawdust will be modeled using a finite-difference model and an analytical solution will be derived to determine the accuracy of the numerical model. This model could be useful for developing fire safety protocols in a factory context by determining the critical thickness of sawdust that leads to spontaneous ignition.